(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
The herb Andrographis paniculata (Burm.f.) Nees has long been integrated into diverse medicinal preparations for its reported analgesic, antipyretic, anti-inflammatory, antidiabetic, antiviral, and anticancer properties. These remedies are also administered to women of reproductive age, including during pregnancy, though information on fetal safety remains limited. A study on developmental toxicity was undertaken in rats to determine the reproductive safety profile of A. paniculata extract for pregnant women. Pregnant Wistar rats were treated orally with A. paniculata extract suspended in 0.25% carboxymethylcellulose at daily doses of 0, 30, 100, or 300 mg/kg from gestation day 7 to day 17. Daily body weight and feed intake were recorded. On day 20, the rats were euthanized to record dam and fetal parameters. The pups were euthanized and processed for skeletal and visceral examinations as per the standard protocol. The body weight gain and total feed intake of rats during the gestation period were unaffected by the treatments. Dam and fetal parameters did not vary significantly in the treated groups compared with the control group. Skeletal evaluations revealed delayed ossification of the sternebrae and ischium, along with occasional rib number anomalies, particularly in the high-dose group. These findings were interpreted as transient developmental delays rather than true teratogenic outcomes. Overall, the preliminary rat study indicated that A. paniculata extract did not produce teratogenic effects.